Integrated Lean-BPM Service Model to Reduce Lead Time of Incorporation of New Employees in a SME of HR Services - Bustillos Andia, Angel Roberto (2022)
The sector of services provided to companies is in a constant search for continuous improvement mainly due to problems presented in the performance of processes, quality of service and time management. The latter is a fundamental piece since the shortest time is always sought in hiring new collaborators to have greater flexibility and maintain a good relationship with customers, achieving a better competitive advantage. Therefore, the integrated Lean-BPM service model is proposed, which aims to reduce the lead time of new employees that is currently 6.22 days generated by poor time management. The mentioned model uses the following tools: standardized work, visual management, business process management and Kanban board, which are adjusted to the identified problems according to the literature review. After applying the method, a 12.88 % reduction was obtained to maintain the efficiency of the integrated model, and the improvement was confirmed by simulation, and similar results were obtained.